Influence of Freezing on the Kinetics of Milk Gelation and the Microstructure of Goat Milk Gel - A. Y. Abdulgamitova; I. T. Smykov (Алматы технологиялық университетінің хабаршысы, 2022)
One of the main problems of goat milk processing is low milk yields, seasonality, the need to accumulate a certain amount of goat milk for processing, difficulties with transportation from remote areas. Freezing of goat's milk for the purpose of its accumulation in the production of fermented dairy products is associated with a change in its properties, which can significantly affect production processes. The aim of this work is to study the effect of freezing–thawing of goat's milk on the kinetics of rennet gelation and the microstructure of the gel in comparison with fresh whole goat's and cow's milk. It is shown that the duration of the primary enzymatic phase of gelation in a sample of thawed goat's milk is close to the duration of the primary phase of raw cow's milk. In the secondary phase of gelation, the final value of the elastic modulus of a clot of thawed goat's milk is close to the value of the elastic modulus of a clot of raw goat's milk.